The 2nd International Laayoune Forum on Biosaline Agriculture 2022
DOI: 10.3390/environsciproc2022016051
|View full text |Cite
|
Sign up to set email alerts
|

How Does Organic Amendment and NPK Fertilization Improve Forage Yield of Cereals under Salinity and Arid Conditions?: Case of Moroccan Sahara

Abstract: This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https:// creativecommons.org/licenses/by/ 4.0/).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…Organic fertilizers also act to form organic acids, which reduce the degree of soil interaction in the plant rhizosphere. This is thought to act to increase the preparation and availability of necessary nutrients such as N and P, and these results are on the one hand consistent with El [6]. Adding organic fertilizer to the soil increased nitrogen and raw phosphorus in the soil.…”
Section: Phosphorus Availabilitysupporting
confidence: 61%
“…Organic fertilizers also act to form organic acids, which reduce the degree of soil interaction in the plant rhizosphere. This is thought to act to increase the preparation and availability of necessary nutrients such as N and P, and these results are on the one hand consistent with El [6]. Adding organic fertilizer to the soil increased nitrogen and raw phosphorus in the soil.…”
Section: Phosphorus Availabilitysupporting
confidence: 61%
“…Additionally, in the absence of adequate potassium fertilization, significant soil K deficiency occurs [15]. Halillat [21] and Belaid [22] have shown that potassium fertilization has a favorable effect on agronomic behavior, including certain characteristics of durum wheat, such as yield and thousand-grain weight.…”
Section: Introductionmentioning
confidence: 99%